2021
DOI: 10.1371/journal.pone.0248599
|View full text |Cite
|
Sign up to set email alerts
|

Strike one hundred to educate one: Measuring the efficacy of collective sanctions experimentally

Abstract: In this paper, we test whether sanctions applied to an entire group on account of the free-riding of one of its members can promote group cooperation. To measure the efficiency of such collective sanctions, we conducted a lab experiment based on a standard public good game. The results show that, overall, collective sanctions are ineffective. Moreover, when subjects are able to punish their peers, the level of cooperation is lower in the regime of collective sanctions than under individual sanctions. Both outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…Sanctions that are perceived as unfair can deter altruistic behaviour (Fehr and Rockenbach, 2003 ). An experiment on sanctions applied to an entire group on account of a single free-rider found that such collective sanctions are ineffective (Chapkovski, 2021 ), corroborating our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Sanctions that are perceived as unfair can deter altruistic behaviour (Fehr and Rockenbach, 2003 ). An experiment on sanctions applied to an entire group on account of a single free-rider found that such collective sanctions are ineffective (Chapkovski, 2021 ), corroborating our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Targeted and collective punishments are both widely used forms of punishment, including in the classroom (e.g., Cushman et al, 2012 ; Darcy, 2010 ; Selman & Dray, 2006 ). A large body of work has examined how collective punishment is used ( Hechter, 1990 ), its effectiveness ( Chapkovski, 2021 ), and how people view collective punishment ( Heckathorn, 1990 ). However, little is known to date about how children evaluate collective punishment when they are themselves impacted by it, such as in a school setting.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons why a teacher might implement collective punishment, such as that the teacher views the whole group or class as an entity, or that the teacher hopes to increase peer pressure and children’s willingness to enforce norms among their peers, to promote a sense of cooperation and cohesion among classmates, or to increase efficiency by punishing the entire group rather than working out who is responsible and how they ought to be punished (e.g., Gao et al, 2015 ; Pereira & van Prooijen, 2018 ). However, if children perceive collective punishment to be unreasonable and unfair, this may lead them to feel angry or resentful, undermine their relationship with their teacher and peers, and thus ultimately work against the teacher’s goals of managing behavior, maintaining order, or fostering cohesion ( Chapkovski, 2021 ). We must thus understand how children perceive and evaluate targeted versus collective punishment and how these forms of punishment may impact children’s relationships with their teachers and peers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collective incentives are also an important part of salary schemes in the form of team incentives (Ledford et al , 1995). There is also some empirical evidence that receiving a bonus lower than an expected amount decreases individuals’ satisfaction (Ockenfels et al , 2014) and that collective punishment is experienced as unfair (Chapkovski, 2021). Additionally, group outcomes, which are typically observed in a much less noisy way, anchor sanctions with collective punishment making the problem of misattribution more severe (Holmström, 1982).…”
Section: Introductionmentioning
confidence: 99%